The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m100099200
|View full text |Cite
|
Sign up to set email alerts
|

The Extra Domain A of Fibronectin Activates Toll-like Receptor 4

Abstract: Cellular fibronectin, which contains an alternatively spliced exon encoding type III repeat extra domain A (EDA), is produced in response to tissue injury. Fragments of fibronectin have been implicated in physiological and pathological processes, especially tissue remodeling associated with inflammation. Because EDAcontaining fibronectin fragments produce cellular responses similar to those provoked by bacterial lipopolysaccharide (LPS), we examined the ability of recombinant EDA to activate Toll-like receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
716
2
13

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,086 publications
(753 citation statements)
references
References 24 publications
14
716
2
13
Order By: Relevance
“…We suggest that once inflammation within the joint causes joint destruction, a variety of molecules are released, such as ED-A of fibronectin, HSPs, and HMGB-1. Each of these molecules is highly expressed in the rheumatoid joint, and each is capable of activating TLR-2 and/or TLR-4 (22)(23)(24)(25)(26)(27)(28)(29). Therefore, once joint damage occurs, a selfperpetuating process, mediated by TLR ligation by endogenous ligands, may be established that promotes the chronic, progressive destruction mediated by the continued activation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that once inflammation within the joint causes joint destruction, a variety of molecules are released, such as ED-A of fibronectin, HSPs, and HMGB-1. Each of these molecules is highly expressed in the rheumatoid joint, and each is capable of activating TLR-2 and/or TLR-4 (22)(23)(24)(25)(26)(27)(28)(29). Therefore, once joint damage occurs, a selfperpetuating process, mediated by TLR ligation by endogenous ligands, may be established that promotes the chronic, progressive destruction mediated by the continued activation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial PG was identified in RA synovial tissue by a monoclonal antibody, particularly in macrophages and antigen-presenting cells (20,21). Additionally, endogenous mammalian TLR agonists, including fibrinogen, extra domain A (ED-A) of fibronectin, Hsp60 and Hsp70, low molecular weight fragments of hyaluronic acid, and high mobility group box chromosomal protein 1 (HMGB-1), a highly conserved nuclear protein that stabilizes nucleosome formation, are expressed in the RA joint, and each has been shown to activate NF-B through TLR-4 and/or TLR-2 (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Recognition of endogenous ligands by TLRs is also an area of active investigation due to its potential relevance to autoimmune diseases, noninfectious inflammatory disorders, and elimination of neoplastic or damaged cells. A number of putative endogenous TLR ligands have already been studied in vitro, including heat shock protein 60 (Hsp60), 78 fibronectin, 79 and the extra domain A of fibrinogen. 80 Recent data have also demonstrated that low-molecular weight soluble hyaluronan (sHA) fragments derived from the extracellular matrix at sites of inflammation are able to induce DC maturation in vitro as well as in vivo through TLR4.…”
Section: Future Directionsmentioning
confidence: 99%
“…TLR‐4 is activated by the recognition of not only pathogen‐associated molecular patterns, such as bacterial lipopolysaccharide (LPS),17 but also endogenous host‐derived ligands including heat shock protein 60 (HSP60), high‐mobility group box 1 (HMGB‐1), extradomain degradation products of the extracellular matrix (ECM), and free fatty acids (FFA) in innate immunity 14, 15, 16, 18, 19, 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%